Dampak polarisasi media sosial terhadap partisipasi politik pemilih muda di Indonesia - Noviana, Velani Laily (Maliki Interdisciplinary Journal, 2026)
The rapid growth of social media in Indonesia has brought complex implications for political participation, particularly among young voters. This study aims to analyze how polarization in the digital space affects the quality of political engagement among young Indonesian voters. Employing a library research approach, this study examines the mechanisms of digital polarization, patterns of disinformation spread, and their impact on the political behavior of the younger generation. The findings indicate that filter bubble and echo chamber mechanism embedded in platform alghoritms foster ideological, affective, and news audience polarization, shifting young voters political participation from rational and reflective to reactive and emotional. This condition is exacerbated by low digital literacy and the rampant spread of hoaxes and disinformation, which ultimately erode young people`s trust in formal democratic institutions. The study recommends strengthening digital literacy, reforming platform regulations, revitalizing the role of democratic institutions in digital spaces, and renewing national narratives grounded in Pancasila values as an integrated strategy to build a healthier and more democratic digital political ecosystem.